Influence of Body-suspended Drive System on Dynamic Characteristics of High-speed Train - GUO Yuxuan; YANG Jianwei; WANG Jinhai (Chengshi guidao jiaotong yanjiu)
［Objective］ As the power source and force transmission component of rail transit vehicles, the drive system influences the dynamic characteristics of the vehicle system to a certain extent. Therefore, it is necessary to conduct research on it. ［Method］ A dynamic model of a single vehicle section from a certain type of high-speed train that uses body-suspended drive system in China is established by the multi-body dynamics simulation software SIMPACK. Based on the simulation analysis, the influence of the body-suspended drive system on the vehicle safety and ride comfort, as well as on the vibration acceleration of the bogie frame and the vehicle body are studied. ［Result & Conclusion］ The body-suspended drive system has different degrees of influence on the operation safety and ride comfort of the vehicle. Except for the lateral stability index, all the other indexes increase with the rise of the vehicle running speed. The body-suspended drive system increases the lateral and vertical vibration acceleration of the bogie frame, and the vertical vibration acceleration of the vehicle body, meanwhile reduces the lateral vibration acceleration of the vehicle body. Moreover, the body-suspended drive system has more significant impact on the vehicle components in the vertical direction than in the lateral direction. The natural frequency of body-suspended traction motor may be reflected on the vehicle body, so the resonance between the motor and the vehicle body needs to be avoided.